Customer value as a key concept for enhancing the customer insight in academic libraries - Niemi-Grundström, Minna (Qualitative and Quantitative Methods in Libraries; Vol 10 No 4 (2021): December issue 2021, 2022)
Abstract: In this paper I will explore how the concept of customer value and its dimensions can be utilized in customer-oriented service design and management in an academic library. Knowing the customers and their needs is one of the most important success factors in successful service design. Understanding the different customers' objectives, wishes, habits and the problems of the everyday life better will give tools to the library to develop its services into a right direction.   I will propose that by identifying customer value propositions a library can enhance the customer understanding and find new angles to evaluate and develop the services. It is a precondition for the successful service and operational development to understand what produces the value to the customers and what does not. Finally, one can state that always the mere understanding is not enough if for example the resources or know-how are not enough for the answering the needs. The critical examination is therefore necessary also for those matters which can produce clear harm to the customers instead of the advantage.